Implementation of Mastery Learning in Improving Student's Understanding of Islamic Religious Education Subjects at SMA Negeri 2 Sigi - Bahdar Bahdar; Juraid Juraid; Ahmad Syahid (Universitas Muhammadiyah Palu, 2022)
Background: This research is an educator-centered learning method implemented in Islamic religious education learning, which some education experts consider in the country as the cause of not achieving the learning objectives as a whole. New educator-centered understanding can realize one learning goal: the knowledge aspect, while the spiritual, social, and skill aspects are still neglected. The learning method that can recognize all learning objectives is mastery learning. To get a clear picture of mastery learning will be presented in this study. Objective: This study aims to determine the implementation of mastery learning in improving students' understanding can also be considered a learning method that can be implemented to complement the shortcomings of Islamic religious education learning methods so far. Methods: This research approach is descriptive with data collection methods using observation, interviews, and documentation research—the location of this research is SMA Negeri 2 Sigi. Then the data analysis technique used by the researcher is through data reduction, data presentation, data verification, and checking the validity of the data. Results: It is known that the implementation of mastery learning in SMA Negeri 2 Sigi through preparatory steps before the teacher teaches, implementation of knowledge, evaluation, enrichment, and remedial learning. It is also known that mastery learning can improve students' understanding of Islamic religious education subjects. Conclusion: This study concludes that three main things support the implementation of mastery learning in SMA Negeri 2 Sigi. The first is a quality-based curriculum. Local government policies and money. Both human resources and technology. Third, the cooperation of all learning elements by implementing the competitive work method with appropriate rewards.